Galectin-3 regulates UVB-induced inflammation in skin. Issue 2 (May 2020) - Wang, Jen-Yu; Lu, Po-Hsuan; Lin, Wan-Wan; Wei, Yu-Hsuan; Chiu, Ling-Ya; Chern, Schu-Rern; Hung, Chi-Feng; Wu, Nan-Lin
Highlights: Galectin-3 in human keratinocytes positively regulates UVB-induced activation of IL-1β and caspase-1. Galectin-3 modulates UVB-induced expression of reactive oxygen species and COX2 in human keratinocytes. UVB-induced skin inflammation is alleviated in galectin-3 knockout mice compared to wild type mice. Abstract: Background: Galectin-3 is widely expressed in many immunocytes and epithelial cells including skin keratinocytes. Galectin-3 can regulate immunological or inflammatory processes and plays a proinflammatory role in some disease models. Galectin-3 has a role in disorders related to ultraviolet (UV) photodamage such as apoptosis, skin squamous cell carcinoma and basal cell carcinoma. However, the evidence of galectin-3 in UVB-induced skin inflammation is still limited and the underlying molecular mechanism remains elusive. Objective: We aimed to investigate the effects of galectin-3 in human epidermal keratinocytes and in mice after UVB irradiation. Methods: Primary human epidermal keratinocytes with galectin-3 knockdown were used as the in vitro model. ELISA, QPCR, and western blotting were applied to evaluate the released cytokine, mRNA and protein expression. Histologic analysis, measurement of erythema and transepidermal water loss (TEWL) were applied to evaluate UVB-induced skin damage in galectin-3 knockout mice. Results: In UVB-irradiated human keratinocytes, galectin-3 knockdown downregulated the UVB-induced ASC crosslinking, cleavage of caspase-1, and formation of active IL-1β. Galectin-3 knockdown also decreased UVB-induced production of reactive oxygen species, p38 phosphorylation, and COX2 expression in human keratinocytes. After four days of UVB irradiation, galectin-3 knockout mice showed reduced gross erythema, histologic features of tissue inflammation, quantified levels of erythema and TEWL compared to wild type mice. The skin tissue lysate also showed less expression of active IL-1β and COX2 in galectin-3 knockout mice. Conclusion: Galectin-3 may play a positive regulatory role in UVB-induced skin inflammation.